Pengaruh Product Bundling, Kualitas Produk, Dan Kemudahan Akses Informasi Terhadap Keputusan Pembelian Konsumen Mytelkomsel Prabayar Di Kota Batam - Rivaldo Antoni Polamolo; Wasiman Wasiman (Pascasarjana STIE Amkop Makassar, 2025)
This study aims to examine the influence of product bundling, product quality, and ease of information access on the purchasing decisions of MyTelkomsel Prepaid users in Batam City. Data were collected through the distribution of online questionnaires accessible via Google Form. The collected data were then analyzed using SPSS version 25. The analysis revealed that all three independent variables, both simultaneously and partially, had a positive and significant effect on purchasing decisions. The F-value of 78.614 with a significance level of 0.000 indicates a strong collective influence. These findings highlight the importance of developing marketing strategies that include attractive product bundling, improved service quality, and ease of information access to drive consumer purchasing decisions through digital platforms. Keywords: Product Bundling, Product Quality, Ease of Access to Information, Purchasing Decisions.